2005
DOI: 10.1055/s-2005-921031
|View full text |Cite
|
Sign up to set email alerts
|

Biopsy of Colorectal Polyps Is Not Adequate for Grading of Neoplasia

Abstract: Biopsy-based diagnosis underestimated histopathological diagnosis in about 10% of colorectal adenomas detected by flexible sigmoidoscopy screening, but advanced neoplasia was underestimated in more than 60%. Efforts must be made to obtain polypectomy specimens to secure precise diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 7 publications
2
35
0
2
Order By: Relevance
“…Pugliese et al [13] reported that among 53 patients with 59 colorectal polyps (≥ 5 mm), seven cases had carcinomas that had invaded the submucosa or beyond, and four of these had been underestimated from the cold biopsy specimens. Gondal et al [14] reported that among 442 patients with a total of 532 colorectal adenomas (≥ 2 mm) biopsied by flexible sigmoidoscopy and removed by colonoscopy, the assessment of the intraepithelial neoplasia status was changed in 51 adenomas (10%), and 38 (7%) of these had been underestimated from the cold biopsy diagnoses compared with the diagnoses based on polypectomy samples. Of these lesions, 389 (73%) were < 10 mm in diameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pugliese et al [13] reported that among 53 patients with 59 colorectal polyps (≥ 5 mm), seven cases had carcinomas that had invaded the submucosa or beyond, and four of these had been underestimated from the cold biopsy specimens. Gondal et al [14] reported that among 442 patients with a total of 532 colorectal adenomas (≥ 2 mm) biopsied by flexible sigmoidoscopy and removed by colonoscopy, the assessment of the intraepithelial neoplasia status was changed in 51 adenomas (10%), and 38 (7%) of these had been underestimated from the cold biopsy diagnoses compared with the diagnoses based on polypectomy samples. Of these lesions, 389 (73%) were < 10 mm in diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Of these lesions, 389 (73%) were < 10 mm in diameter. In addition, four carcinomas invading the submucosa or beyond had been underestimated as being low-grade or high-grade intraepithelial neoplasias [14] . These observations suggest that cold biopsy-based diagnoses underestimate histopathologic diagnoses of the resected lesions in some cases of colorectal epithelial neoplastic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the rate of adenocarcinoma in adenomas in biopsies is underestimated when compared with later total polypectomy (15,16). The excision margins have also been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, biopsybased diagnosis has underestimated histopathological diagnosis in about 10% of colorectal adenomas and more than 60% of advanced neoplasia. So it is important to obtain whole polypectomy specimens to get a correct diagnosis [29].…”
Section: Discussionmentioning
confidence: 99%